Linarine inhibits inflammatory responses in dry eye disease mice by modulating purinergic receptors - Liu, Pei; Jiang, Pengfei; Tan, Kang; Yu, Yunfeng; Qin, Genyan; Liu, Tingting; Tian, Sainan; Peng, Jun; Peng, Qinghua (Frontiers in Immunology, 2024)
Background Linarine is a natural chemical component widely found in Buddleja officinalis Maxim., Chrysanthemum indicum L., Mentha canadensis L., and other medicinal plants. Modern pharmacological studies have shown that linarine with good anti-inflammatory and antioxidant activities can inhibit the proliferation and induce apoptosis of many kinds of tumor cells. Moreover, linarine showed protective effect on the liver, kidneys, and other organs. Methods Inflammation model of human corneal epithelial cell (HCEC) was constructed using NaCl induction, and cytotoxicity was detected by the CCK8 assay. The levels of inflammatory factors tumor necrosis factor-α (TNF-α) and interleukin 1β (IL-1β) were measured using Enzyme-linked immunoassay (ELISA). Chronic painful stimulation (tail clamping) in combination with Benzalkonium Chloride Solution drops in a desiccator established a mouse model of dry eye disease (DED). The following parameters were recorded: body mass, anal temperature, tear secretion, tear film rupture time, and corneal fluorescein staining. The levels of inflammatory factors mitogen activated protein kinase (MAPK), nuclear factor kappa-B (NF-kB), c-Jun N-terminal kinase (JNK), IL-1β, Interleukin 18(IL-18), A2A, A3, P2X4, P2X7, P2Y1 were measured by using immunofluorescence (IF) staining. Results Linarine can inhibit the secreation of TNF-α, and IL-1β in HCECs. Linarine prolonged tear film rupture time, promoted tear secretion, repaired corneal damage, and reduced the levels of inflammatory factors of MAPK, NF-kB, JNK, IL-1β, IL-18, and modulated the levels of the purinergic receptor. Conclusions Linarine is effective in treating dry eye in mice by inhibiting purinergic receptors-mediated inflammatory response.